GAMIFICATION IN ENGLISH LANGUAGE LEARNING: ENHANCING MOTIVATION AND ENGAGEMENT (Scientific journal of the Fergana State University, 2025)
This article examines the essential factors that contribute to engaging students in the process of learning English through the use of game-based programs. In today’s rapidly changing world, advancements in education have created new opportunities not only for mastering modern technologies but also for acquiring foreign languages. One innovative approach, known as gamification, creates a more comfortable learning environment for young people and allows them to absorb material through diverse methods, helping to avoid monotonous instruction and overwhelming vocabulary loads. Incorporating game mechanics into the educational process assists learners in overcoming psychological barriers and reducing anxiety during academic tasks. This approach fosters a stable and lasting interest in studying English. Increased engagement in interactive, game-based activities significantly enhances the effectiveness of language acquisition, ensuring alignment with modern educational standards and keeping pace with current developments in teaching methods. Additionally, the gamified learning model promotes the development of communication skills by encouraging students to collaborate in group activities and creating a positive, cooperative classroom atmosphere. The research demonstrates that integrating game-based exercises into language education improves the overall quality of knowledge retention, nurtures positive motivation